DOMINASI PEMERINTAH SINGAPURA DALAM LIBERALISASI EKONOMI - Khamidatul Helmia (HI 16 UMY 016, 2016)
*16 This skripsi explains how Singapore government preserved dominant intervention in liberal Singapore economic development under three prime ministers, that is Prime Minister Lee Kuan Yew (1965-1990), Prime minister Goh Chok Tong (1990-2004), and Prime minister Lee Hsein Loong (2004-2012). In analyzing the main topic in this skripsi, the researcher used state capitalism concept. The concept explained the important roles of government agencies in executing commercial economic activity where the government agencies will act like a government’s company and has dominant role in that country. As a country with lack of natural resource, Singapore demands its country to be open-minded with market economic system and free market to be able to draw foreign interest. The majority of countries in the world which applying market economic system will indirectly decrease the level of the government intervene in economic development. Different from Singapore, the authoritarian attitude of People’s Action Party (PAP) succeeds in creating politic stability inside the country which has impact on the government’s success to keep its domination in liberal Singapore’s economic development. The domination is conducted through government’s economic agencies such as statutory board agency and government’s companies. Through economic agencies, the government becomes the capital owner and shareholder, thus the government can control the investment. The domination works in making Singapore as one of the developed countries, particularly in South East.